2014
DOI: 10.1210/jc.2013-3222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tomato and Soy on Serum Adipokine Concentrations in Postmenopausal Women at Increased Breast Cancer Risk: A Cross-Over Dietary Intervention Trial

Abstract: Increasing dietary consumption of tomato-based foods may beneficially increase serum adiponectin concentrations among postmenopausal women at increased breast cancer risk, especially those who are not obese. Additional studies are essential to confirm these effects and to elucidate the specific mechanisms that may make phytonutrients found in tomatoes practical as breast cancer chemopreventive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“… 57 Furthermore, studying the protein expression of several inflammatory markers in situ has the advantage of indicating local mechanisms by which the antioxidant is more likely to act on in the breast tissue. Unlike previous studies that have measured these markers in the blood, 17 - 22 our assessments may better reflect the local breast microenvironment since measures are directly obtained from the breast source. However, with these types of analyses, the risk of statistical multiplicity increases, which increases the likelihood of rare events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 57 Furthermore, studying the protein expression of several inflammatory markers in situ has the advantage of indicating local mechanisms by which the antioxidant is more likely to act on in the breast tissue. Unlike previous studies that have measured these markers in the blood, 17 - 22 our assessments may better reflect the local breast microenvironment since measures are directly obtained from the breast source. However, with these types of analyses, the risk of statistical multiplicity increases, which increases the likelihood of rare events.…”
Section: Discussionmentioning
confidence: 99%
“…Among the few studies that examined the association between antioxidant intakes and circulating levels of inflammatory markers (3 observational 17 - 19 and 3 experimental 20 - 22 ), intakes of retinol, carotenoids, lycopene, vitamin C or E tended to be negatively associated with C-reactive protein (CRP), 17 , 18 , 20 interleukin (IL)-1β, 19 or leptin 21 and positively associated with adiponectin. 21 However, since inflammatory marker concentrations were obtained from blood analysis, these may not adequately reflect levels found in the tumor microenvironment (breast tissue). Indeed, studies have shown that circulating levels of inflammatory markers such as leptin, adiponectin, and transforming growth factor (TGF)-β differ from concentrations measured in mammary tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Our data provides additional evidence for a biological link between menopausal status, hereditary factor, BMI and breast cancer, suggesting an independent role of different circulating adiponectin in the carcinogenesis of breast cancer. In addition, because circulating adiponectin can be influenced by a number of behavioral and drug interventions, such as fruit, weight loss, the observation in this study may help guide a preventive strategy for breast cancer[ 29 31 ]. Further investigation into the association between HMW adiponectin, HMW/total adiponectin ratio, the participation of the different receptors, and ADIPOQ polymorphisms are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…По данным других исследователей, каждые 10 г ПВ в питании достоверно на 7 % снижали риск развития РМЖ [29]. Исследования американских эндокринологов [30] показали достоверное повышение концентрации адипонектина на фоне дополнительного обогащения рациона питания продуктами, содержащими томат (более 25 мг ликопина), в группе женщин с повышенным риском РМЖ. Чем больше употребление адипонектина, тем меньше риск РМЖ, особенно у женщин в постменопаузе.…”
Section: результаты и обсуждениеunclassified